Effects of an integrated intervention on schistosomiasis prevalence in a rural area of Tanzania. - Yoonho Cho; Jungim Lee; Humphrey Deogratias Mazigo; Leah Elisha Salamba; Seungman Cha (PLoS Neglected Tropical Diseases, 2025)
Neglected tropical diseases have a huge impact around the world, particularly in sub-Saharan Africa. The global NTD community and countries have emphasized the importance of integrated interventions. However, findings on effectiveness of integrated interventions have been inconsistent. The study was a quasi-experimental design with repeated cross-sectional data collected from both intervention and control groups in 2020 and 2022. School-aged children from 12 schools were divided into three groups: the school-based mass drug administration (MDA) group, the school-based and community-based MDA group, and the integrated model group. A multilevel logistic regression model was employed to assess the impact of the integrated intervention on schistosomiasis prevalence, with individuals as the first level and groups as the second level. Examining the effect of the intervention on the prevalence of schistosomiasis among students, both the school-based and community-based MDA group (risk difference [RD] -13.7%; 95% confidence interval [CI] -24.5% to -2.9%; p < .05) and the integrated model group (RD -23.3%; 95% CI -32.7% to -13.9%; p < .001) showed significantly greater reductions compared to the school-based MDA alone group. In addition, the integrated model group (RD -9. 6%; 95% CI -23.3% to 4.1%; p > .05) had a greater reduction in infection rates than the school-based and community-based group. For behavior change outcomes, when comparing changes in the proportion of water contact behaviors, the integrated model group had a significantly greater reduction compared to the school-based and community-based group (RD -56.0%; 95% CI -67.3% to -44.8%; p < .05). When comparing the change in home toilet use between groups, the fully integrated model group performed significantly better than the other two groups. This study found that an integrated approach to S. haematobium elimination was consistently effective in both students and adults. Further research is required to better understand the effectiveness of integrated NTD control strategies and where improvements are needed.